Mobilising UNESCO chairs in natural sciences for policy action towards the 2030 agenda - Trembley, Leo; Goncharova, Nadezhda V. (Journal of the Belarusian State University. Ecology, 2019)
The results of the Geneva conference held on July 5–7, 2017, organized in connection with the 25th anniversary of UNESCO's UNITWIN / UNESCO Chairs program, aimed at facilitating the effective collaboration of the UNESCO Chairs in Natural Sciences among themselves, as well as with UNESCO in the implementation of the Sustainable Development Goals (SD) of the Agenda day in the field of sustainable development for the period until 2030.
Keywords: UNESCO; management; environment; ecology; sustainable development; ecological education